Relevansi Pemikiran Pendidikan Islam KH. Ad. Rahman Syakur di Era Kontemporer - Mukaromah, Ning (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
Studies on Islamic education in Indonesia have predominantly focused on nationally recognized intellectual figures, while the contributions of local pesantren scholars remain underexplored in academic discourse. This article examines the relevance of the educational thought of KH. AD. Rahman Syakur in addressing contemporary educational challenges. Using a qualitative library research approach, the study analyzes Sajadah Khidmah: Meneladani Khidmah dan Keistiqamahan KH. AD. Rahman Syakur as the primary source, supported by scholarly literature on Islamic education and pesantren traditions. Data were examined through descriptive qualitative content analysis. The findings indicate that KH. AD. Rahman Syakur’s educational thought emphasizes khidmah-based education, moral and ethical formation (akhlaq and adab), teacher exemplarity, and the integration of religious knowledge with social realities through community-oriented fiqh. These principles remain highly relevant in responding to technological disruption, moral decline, and the increasing commercialization of modern education. The study highlights the importance of reconstructing local pesantren scholarship as a contextual, humanistic, and socially transformative model of Islamic education.